AKTIVITAS FISIK DENGAN KEJADIAN INSOMNIA PADA ATLIT GYM - Manggopa, Rafli; Kundre, Rina; Katuuk, Mario (JURNAL KEPERAWATAN, 2019)
Abstract : Insomnia is a difficulty in starting and maintaining sleep so someone cannot meet adequate sleep needs, both quantity and quality. Physical activity is a body movement produced by skeletal muscle which results in energy expenditure, regular physical activity has long been considered an important component in healthy living. The purpose of this study was to determine the relationship between physical activities and the incidence of insomnia experienced by Manado Global gym athletes. The research method used was observational analytic with cross sectional design. The sampling technique in this study was total sampling with 100 samples. Data collection is done using a questionnaire. The research result based on statistic test of Chi-Square test with the level of meaning 95% (Î± = 0,05) is presented on a table 2x3 with earned value Ñ€ = 0,000 which is smaller than Î± (0,05) with rejected Ho and accepted Ha. The conclusion shows that there is a correlation between physical activities and insomnia condition experienced by Global Manado gym athletes. Keywords : Physical activity, insomnia incident Abstrak : Insomnia merupakan kesukaran dalam memulai dan mempertahankan tidur sehingga tidak dapat memenuhi kebutuhan tidur yang adekuat, baik kuantitas maupun kualitas. Aktivitas fisik merupakan gerakan tubuh yang dihasilkan oleh otot rangka yang mengakibatkan pengeluaran energi, aktivitas fisik secara teratur telah lama dianggap sebagai komponen penting dalam hidup sehat. Tujuan penelitian ini untuk mengetahui hubungan aktivitas fisik dengan kejadian insomnia pada atlit gym Global Manado. Metode penelitian yang digunakan yaitu observasional analitik dengan rancangan cross sectional. Teknik pengambilan sampel pada penelitian ini yaitu total sampling dengan jumlah 100 sampel. Pengumpulan data dilakukan menggunakan kuesioner. Hasil penelitian berdasarkan uji statistik Chi-Square test dengan tingkat kemaknaan 95% (Î± = 0,05) disajikan dalam tabel 2x3 diperoleh nilai Ñ€ = 0,000 yakni lebih kecil dibandingkan Î± (0,05) dengan Ho ditolak dan Ha diterima. Kesimpulan terdapat hubungan aktivitas fisik dengan kejadian insomnia pada atlit gym Global Manado. Kata kunci : Aktivitas fisik, Kejadian Insomnia